2009
DOI: 10.1016/j.neurobiolaging.2007.05.025
|View full text |Cite
|
Sign up to set email alerts
|

Protection against β-amyloid induced abnormal synaptic function and cell death by Ginkgolide J

Abstract: A new Ginkgo biloba extract P8A (TTL), 70% enriched with terpene trilactones, prevents Aβ 1-42 induced inhibition of long-term potentiation in the CA1 region of mouse hippocampal slices. This neuroprotective effect is attributed in large part to ginkgolide J that completely replicates the effect of the extract. Ginkgolide J is also capable of inhibiting cell death of rodent hippocampal neurons caused by Aβ 1-42 . This beneficial and multi-faceted mode of action of the ginkgolide makes it a new and promising le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
24
0
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(26 citation statements)
references
References 54 publications
1
24
0
1
Order By: Relevance
“…These features of ginkgolides fit the proposed pharmacophore of hPXR ligands, which includes a molecular mass Ͼ300 Da, an ability to form hydrophobic interactions (e.g., aromatic -interactions), and the presence of hydrogen bond acceptors (one or two) and hydrogen bond donors (Xiao et al, 2011). Although molecular docking analysis predicts that ginkgolide J, which is bioactive (Vitolo et al, 2009), binds very weakly to the ligand-binding domain of the receptor, it does not activate hPXR, as shown in the various assays conducted in the present study. However, it is possible that ginkgolide J is capable of acting as an antagonist of hPXR, but future studies are needed to address this issue.…”
Section: Discussionmentioning
confidence: 68%
See 1 more Smart Citation
“…These features of ginkgolides fit the proposed pharmacophore of hPXR ligands, which includes a molecular mass Ͼ300 Da, an ability to form hydrophobic interactions (e.g., aromatic -interactions), and the presence of hydrogen bond acceptors (one or two) and hydrogen bond donors (Xiao et al, 2011). Although molecular docking analysis predicts that ginkgolide J, which is bioactive (Vitolo et al, 2009), binds very weakly to the ligand-binding domain of the receptor, it does not activate hPXR, as shown in the various assays conducted in the present study. However, it is possible that ginkgolide J is capable of acting as an antagonist of hPXR, but future studies are needed to address this issue.…”
Section: Discussionmentioning
confidence: 68%
“…For example, ginkgolide B and ginkgolide C are more efficacious than ginkgolide A and ginkgolide J in antagonizing the glycine-gated chloride channel (Ivic et al, 2003). Ginkgolide B (Xiao et al, 2010) and ginkgolide J (Vitolo et al, 2009) also inhibit ␤-amyloid-induced cell death in rodent hippocampal neurons. Other actions of ginkgolide B include antagonism of platelet-activating factor receptor and antiapoptotic, anti-inflammatory, antioxidant, and antiproliferative activities (Xia and Fang, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Many recent reports confirm that ginkgolide compounds, the most important constituents of Ginkgo biloba, have free radical-scavenging activity against hydroxyl radicals and superoxide anions [13,14]. Recently, Vitolo et al [15] found that the activity of natural ginkgolides was determined by their cage-like structure and hydroxyl group location in cell death of rodent hippocampal neurons caused by amyloid beta 1-42. As we know, platelet-activating factor (PAF) is a bioactive phospholipid that accumulates during I/R and is involved in the activation of platelets, neutrophils and pro-inflammatory signaling, which is suggested to enhance brain I/R damage.…”
Section: Introductionmentioning
confidence: 99%
“…Up to now, flavones glycosides, terpene lactones and other chemical components have been separated from and identified in Ginkgo biloba extracts Dew et al, 2013). Previous studies have shown that ginkgolide A, ginkgolide B, ginkgolide C, ginkgolide J, and ginkgolide K all have neuroprotective effects and antioxidative properties, especially on neuron injuries induced by cerebral ischemia Qin et al, 2014;Ma et al, 2012a,b;Numa et al, 2007;Vitolo et al, 2009). Interestingly, ginkgolide activities, particularly in protecting against cerebral ischemia injury, were found to be affected by the chemical structure of ginkgolide (Ma et al, 2012).…”
Section: Introductionmentioning
confidence: 99%